1992
DOI: 10.1002/j.1460-2075.1992.tb05376.x
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus infection of cells arrested in the cell cycle.

Abstract: Cell proliferation is necessary for proviral integration and productive infection of most retroviruses. Nevertheless, the human immunodeficiency virus (HIV) can infect non‐dividing macrophages. This ability to grow in non‐dividing cells is not specific to macrophages because, as we show here, CD4+ HeLa cells arrested at stage G2 of the cell cycle can be infected by HIV‐1. Proliferation is necessary for these same cells to be infected by a murine retrovirus, MuLV. HIV‐1 integrates into the arrested cell DNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
290
2
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(303 citation statements)
references
References 38 publications
5
290
2
6
Order By: Relevance
“…The capacity to replicate in non-dividing cells is a specific feature that distinguishes lentiviruses from murine and avian retroviruses, which require nuclear membrane breakdown during mitosis for viral cDNA integration (Lewis et al, 1992;Roe et al, 1993). Some studies have suggested that only macrophages that maintain proliferative capacity can support productive HIV-1 infection (Kootstra and Schuitemaker, 1998;Schuitemaker et al, 1994).…”
Section: Nuclear Importmentioning
confidence: 99%
“…The capacity to replicate in non-dividing cells is a specific feature that distinguishes lentiviruses from murine and avian retroviruses, which require nuclear membrane breakdown during mitosis for viral cDNA integration (Lewis et al, 1992;Roe et al, 1993). Some studies have suggested that only macrophages that maintain proliferative capacity can support productive HIV-1 infection (Kootstra and Schuitemaker, 1998;Schuitemaker et al, 1994).…”
Section: Nuclear Importmentioning
confidence: 99%
“…[1][2][3][4] Lentiviral vectors have the unique feature of being able to transduce nondividing cells, making it particularly attractive for certain gene therapy applications. [5][6][7] Sometimes, to achieve a desirable therapeutic effect, the viral vectors must be capable of precisely delivering a gene of interest to specific cells without influencing non-target cells. [8][9][10] Many efforts have been made to develop such targeting viral vector systems mostly by altering the viral envelope glycoprotein.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the restrictions observed in G 0 T-cells, nuclear import [Bukrinsky et al, 1992] and integration [Weinberg et al, 1991] were demonstrated in G 1 /S-phase arrested T-cell lines and non-cycling monocyte/ macrophages, respectively. These seminal studies and others [Lewis et al, 1992;Lewis and Emerman, 1994] established that HIV-1 can complete the early steps, including integration, in these non-cycling cells. The ability of HIV-1 to productively infect non-cycling macrophages (see below) is thought to be an important step in establishing human infection, as well perhaps providing a long term virus reservoir.…”
Section: Questions Methods and Implicationsmentioning
confidence: 94%